Triumph over predatory lending: the jihad of the consumer champions of Keramat - Zaba, Muhammad Amirul Husni; Elberberi, Ola Ali Amin; Saquib, Nazmus; Mhd. Sarif, Suhaimi (IIUM Press, 2023)
The Birth of The Consumer Champions of Keramat narrates the inspiring journey of a group of passionate local activists who come together to challenge the unscrupulous practices of predatory lending in the bustling neighborhood of Keramat. Driven by a desire to protect the rights of consumers and advocate for financial justice, Ahmad, Salleh, Jamil, and others establish "The Consumer Champions of Keramat." Their vision is to create a safer, more informed community, free from the clutches of loan sharks known as "Ah Longs." The activists conduct educational workshops, seminars, and community events to empower residents with financial literacy and knowledge about responsible borrowing. Harnessing the power of social media, they launch a compelling campaign, sharing personal stories that ignite empathy and raise awareness about the impact of predatory lending. The campaign not only inspires change but also draws support from the local community and even government officials. However, their advocacy is met with intimidation tactics from the Ah Longs, but the activists remain resilient, supported by their community. Despite facing challenges, The Consumer Champions of Keramat continue to make a difference, advocating for stricter regulations and working towards a debt-free community.